BETON DENGAN SUBSTITUSI SEMEN BERBASIS TERAK NIKEL - Nuroji Nuroji; Supriyadi Supriyadi; Han Ay Lie; Sie Alexander Patrick Subagyo (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2022)
This research studied the effect of nickel-based cement substitution in concrete to analyze its behavior. The percentage of substituted nickel-slag was 10%, 20% and 30% to the cement weight. The mechanical properties studied were the compression f'c and tensile fMR stresses at the ages of 14, 28, 42 and 56 days. The data were analyzed and the visual observation of the fractured plans were addressed to determine the failure modes. The research concluded that the nickel-slag cement reduced both the compressive and tensile strength as a function of the substituted content, the decrease process followed a linear path. It was found that the strength of nickel-slag concrete cannot be defined at 28 days due to a prolonged chemical process.